2016
DOI: 10.1016/j.cub.2016.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of DNA Replication Reveals Dynamic Plasticity of Large-Scale Chromatin Fibers

Abstract: Summary In higher eukaryotic interphase nuclei, the 100s-1000s fold linear compaction of chromatin is difficult to reconcile with its function as a template for transcription, replication, and repair. It is challenging to imagine how DNA and RNA polymerases with their associated molecular machinery would move along the DNA template without transient decondensation of observed large-scale chromatin “chromonema” fibers [1]. Transcription or replication “factory” models [2] in which polymerases remain fixed while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
(30 reference statements)
2
23
1
Order By: Relevance
“…A previous study proposed that TetO or LacO repeats bound by their corresponding repressors can cause replication fork barrier, accompanied by unusual, long-lived PCNA foci overlying the operator repeats, followed by mitotic defects ( 54 ). This previous study is inconsistent with other published studies, including live-cell imaging of LacO and PCNA dynamics during S-phase, which demonstrated that chromosome regions carrying large numbers of LacO arrays replicated at specific times during the cell cycle without any delay in DNA replication ( 55 , 56 ).…”
Section: Resultscontrasting
confidence: 99%
“…A previous study proposed that TetO or LacO repeats bound by their corresponding repressors can cause replication fork barrier, accompanied by unusual, long-lived PCNA foci overlying the operator repeats, followed by mitotic defects ( 54 ). This previous study is inconsistent with other published studies, including live-cell imaging of LacO and PCNA dynamics during S-phase, which demonstrated that chromosome regions carrying large numbers of LacO arrays replicated at specific times during the cell cycle without any delay in DNA replication ( 55 , 56 ).…”
Section: Resultscontrasting
confidence: 99%
“…In contrast, a recent study in mammalian cells suggests that large‐scale chromatin remodeling is not needed during replication. This model proposes a mechanism by which only very transient, local decompaction of replicating regions takes place, and that epigenetic marks can be transferred from template DNA to the nearby newly replicated DNA . This study concludes that there is a ‘relatively disordered’ internal structure for chromatin fibers.…”
Section: Genome Organization Before Mitosismentioning
confidence: 81%
“…Microscopy has also revealed that chromosomes occupy distinct territories, and that TADs along individual chromosomes are spatially segregated into GC‐rich transcriptionally active chromatin regions in the interior of the nucleus and GC‐poor transcriptionally inactive regions at the nuclear periphery . The gene rich regions display a visually spread out conformation in comparison with gene poor regions, though recent light and electron microscopy results suggest that fairly compact fiber structures exist for both active and inactive genomic regions . To understand the impact of genome structure changes that happen during and after mitosis, it is important to note the stability of the 3D genome structures during interphase.…”
Section: Genome Organization Before Mitosismentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of these algorithms, conventional microscopy uses deconvolution to improve the quality of images as in confocal microscopy [12]. For example, deconvolution was applied to wide-field microscopy images to resolve DNA replication units that are studied only by electron and structured illumination microscopy [13]. Unlike these later methods, confocal and classical light microscopy possesses the ability to study these structures in the living cells.…”
Section: Introductionmentioning
confidence: 99%